The effects of budget goals and task interdependence on the level of and variance in performance: a research note - Hirst, Mark K; Yetton, Philip W (Accounting, Organizations and Society, 1999)
The effects of goal setting and task interdependence on both the level of and variance in performance are examined using a laboratory, resource allocation task. The results show, consistent with existing research, main effects for goal setting and task interdependence on the level of performance, but no goal setting by task interaction effect as hypothesised. The results also show that an increase in task interdependence increases performance variance but that goal setting reduces it with important implications for budget setting.